PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP PERILAKU AGRESIF VERBAL SISWA DI SMP NEGERI 5 KOTA JAMBI - Andini, Yuliza Dwi; Gutji, Nelyahardi; Harahap, Nur Hasanah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This research was motivated by the phenomenon of students behaving verbally aggressively at SMP Negeri 5 Jambi City. Verbal aggressive behavior itself can be influenced by various factors, one of which is interpersonal communication. The aim of this research is to measure the level of interpersonal communication, the level of verbal aggressive behavior, and to determine the influence of interpersonal communication on verbal aggressive behavior. This research uses quantitative research methods with simple regression analysis. The sampling technique used was the Slovin formula with a total research sample of 285 students. Data collection tools used interpersonal communication questionnaires and verbal aggressive behavior questionnaires with Likert scale measurements. The results of the research show that the significance value is 0.000 < 0.05 and the t value > t table or -13.298 > 1.973, which means that there is a significant influence between interpersonal communication on verbal aggressive behavior, with the direction of the influence being negative.